Are Our FEERs Justified? - Barisone, G; Driver, R; Wren-Lewis, S (School of Business and Economics (University of Exeter), 2000)
The Fundamental Equilibrium Exchange Rate (FEER) method of calculating an equilibrium real exchange rate is the most widely used alternative to PPP. This paper presents the first comprehensive historical test of FEER calculations for six major economies, using estimates for the last twenty years. We focus on unit root and cointegration techniques both at the individual country level and jointly using panel based estimation. Specifically, we test whether real exchange rates cointegrate with time series for the FEER with a coefficient of unity, so that the difference between the FEER and the real exchange rate is stationary. Even at an individual country level, the results provide support for the FEER, particularly in Canada, the UK and Germany. Panel unit root tests suggest that the real exchange rate and FEER cointegrate. Overall the results suggest that, with the possible exception of the US, the FEER approach represents an improvement over PPP in explaining medium to long term trends in the real exchange rates of the major industrialised countries.